2019
DOI: 10.1158/0008-5472.can-18-3927
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D–VDR Signaling Inhibits Wnt/β-Catenin–Mediated Melanoma Progression and Promotes Antitumor Immunity

Abstract: 1a,25-Dihydroxyvitamin D3 signals via the vitamin D receptor (VDR). Higher serum vitamin D is associated with thinner primary melanoma and better outcome, although a causal mechanism has not been established. As patients with melanoma commonly avoid sun exposure, and consequent vitamin D deficiency might worsen outcomes, we interrogated 703 primary melanoma transcriptomes to understand the role of vitamin D-VDR signaling and replicated the findings in The Cancer Genome Atlas metastases. VDR expression was inde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 56 publications
(63 reference statements)
7
57
0
Order By: Relevance
“…[86,91] Stimulation also shown to be dependent on the PDIA3 membrane complex. [61] In contrast, VDR is implicated in vitamin D-triggered downstream regulation of transcriptional activity of WNT, [92][93][94][95] sonic hedgehog signalling molecule (SHH) [96][97][98][99][100][101] and NOTCH [102][103][104] signalling pathways [95] (Figure 2 Another import argument that PDIA3 is involved in vitamin D signalling came from animal knockout studies. Although an ubiquitous Pdia3 deletion in mice is embryonically lethal, [68,75] heterozygous Pdia3 +/knockout mice showed abnormalities in skeletal tissues [68] indicating effects on calcium homeostasis.…”
Section: E Viden Ce For Memb R Ane S I G Nalling Of Vitamin Dmentioning
confidence: 99%
“…[86,91] Stimulation also shown to be dependent on the PDIA3 membrane complex. [61] In contrast, VDR is implicated in vitamin D-triggered downstream regulation of transcriptional activity of WNT, [92][93][94][95] sonic hedgehog signalling molecule (SHH) [96][97][98][99][100][101] and NOTCH [102][103][104] signalling pathways [95] (Figure 2 Another import argument that PDIA3 is involved in vitamin D signalling came from animal knockout studies. Although an ubiquitous Pdia3 deletion in mice is embryonically lethal, [68,75] heterozygous Pdia3 +/knockout mice showed abnormalities in skeletal tissues [68] indicating effects on calcium homeostasis.…”
Section: E Viden Ce For Memb R Ane S I G Nalling Of Vitamin Dmentioning
confidence: 99%
“…It has recently been shown that tumour intrinsic Wnt/β-catenin signaling mediates immune exclusion in melanoma and this has been confirmed across other human cancers [63,64]. Vitamin D-VDR signaling inhibits the Wnt/β-catenin pathway and could be explored therapeutically with the aim of counteracting resistance to immunotherapy [63,64].…”
Section: Immunomodulation and Tumour Inflammatory Responsementioning
confidence: 95%
“…On the other hand, pre-existing antitumour T-cell response is associated with a greater efficacy of immune checkpoint blockade, whereas the so-called immune deserted tumours hardly ever respond to immunotherapy [62]. It has recently been shown that tumour intrinsic Wnt/β-catenin signaling mediates immune exclusion in melanoma and this has been confirmed across other human cancers [63,64]. Vitamin D-VDR signaling inhibits the Wnt/β-catenin pathway and could be explored therapeutically with the aim of counteracting resistance to immunotherapy [63,64].…”
Section: Immunomodulation and Tumour Inflammatory Responsementioning
confidence: 99%
“…Low 1α,25-dihydroxyvitamin D3 and vitamin D receptor ( VDR ) level correlates to increased cancer incidence and melanoma progression, respectively. Recently, it has been shown that high VDR expression correlated with the inhibition of tumour growth, low Wnt/β-catenin activation and the induction of the immune response [ 54 ] ( Table 1 ).…”
Section: Wnt Pathway and Other Cancersmentioning
confidence: 99%